2006
DOI: 10.1002/bip.20624
|View full text |Cite
|
Sign up to set email alerts
|

Honey, I shrunk the DNA: DNA length as a probe for nucleic‐acid enzyme activity

Abstract: The replication, recombination, and repair of DNA are processes essential for the maintenance of genomic information and require the activity of numerous enzymes that catalyze the polymerization or digestion of DNA. This review will discuss how differences in elastic properties between single‐ and double‐stranded DNA can be used as a probe to study the dynamics of these enzymes at the single‐molecule level. © 2006 Wiley Periodicals, Inc. Biopolymers 85: 144–153, 2007.This article was originally published onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 83 publications
(106 reference statements)
0
23
0
Order By: Relevance
“…Given that the longitudinal axis of the eukaryotic MCM2-7 complex comprises ~115 Å (Remus et al, 2009), MCM2-7 should protect ~34 basepairs of dsDNA (115 Å ÷ 3.4 Å per basepair = 34 basepairs), which likely occurs in the context of pre-replication complexes. Importantly, ssDNA can be extended to 1.7 times the length of B-form DNA (Smith et al, 1996; van Oijen, 2007). Therefore, 20 nt (34 ÷ 1.7) of fully extended ssDNA would suffice to traverse the entire MCM2-7 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the longitudinal axis of the eukaryotic MCM2-7 complex comprises ~115 Å (Remus et al, 2009), MCM2-7 should protect ~34 basepairs of dsDNA (115 Å ÷ 3.4 Å per basepair = 34 basepairs), which likely occurs in the context of pre-replication complexes. Importantly, ssDNA can be extended to 1.7 times the length of B-form DNA (Smith et al, 1996; van Oijen, 2007). Therefore, 20 nt (34 ÷ 1.7) of fully extended ssDNA would suffice to traverse the entire MCM2-7 channel.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Such small fragments are involved in DNA packaging around histones, in genetic material loading in viruses (requiring compaction/bending), in gene transcription and regulation (requiring looping), in gene delivery via small volume carriers for gene therapy, and as engineering material components for nanofabrication. It is calculated 11 that in a mammalian-cell nucleus, the concentration of DNA would be $10 mg/ml.…”
Section: -22mentioning
confidence: 99%
“…However, studies by van Oijen and colleagues have used flow-stretched DNA molecules. 3,60 The force exerted on the DNA by the flowing buffer can be calculated based on both the end-to-end length of the DNA as well as the magnitude of the fluctuations exhibited by the beads. Because ssDNA and dsDNA exhibit distinct force-extension profiles, this flow-stretching approach to TPM is particularly well suited to studying systems that involve the conversion of dsDNA to ssDNA or vice versa, such as single molecules of λ exonuclease and single DNA replication forks.…”
Section: Tethered Particle Motion (Tpm)mentioning
confidence: 99%
“…[1][2][3] For example, groundbreaking studies in single-molecule visualization revealed many aspects of the dynamics of F1-ATPase rotary motor, including rotation rates and details of the mechanochemical reaction cycle. [4][5][6][7] Several studies also probed the behavior of mechanoenzymes such as myosin, kinesin and dynein; most prominent were those techniques that measured the step size and force exerted by these proteins as they travel along actin filaments or microtubules.…”
Section: Introductionmentioning
confidence: 99%